All Disease Control Program (All DC) - เหมรัชต์จีระกุล จักรพงษ์ (Journal of Health Science of Thailand, 2022)
Currently, many diseases have developed themselves to be resistant to medicine and heavy environments. Some diseases has infected in the human’s body many years and outbreaks as time goes on. The speed and accuracy in taking disease prevention are the most important to control epidemics of infectious disease but to limitations such as Technology cost the number of staff, etc. makes a difference in the use of technology in some places. Also, the access and storage of information of each service are not integrated into one source. All disease control program (ALL DC) is outbreak data collection program that can help to collect patient data in one source and can install in portable devices such as mobile phones and tablets. The program can collect the accuracy epidemic positions by device’s GPS (Global Positioning System), stored online, alert local officers through the line program, summarize data and report in one step. The results showed that the epidemic position could be guided to the patient’s home based on the location coordinates recorded with accuracy. The patient information could be displayed with pictures, details of disease control with comparison chart each month completely. The results of dengue fever comparison before and after using the program showed that the rate of dengue patients (2016-2019) decreased, Officers were very satisfied. Currently, the program has been used in Sanitariums and Primary care units (PCU) and plan to expand to Songkhla hospital network.